Hypothermia-Induced Ubiquitination of Voltage-Dependent Anion Channel 3 Protects BV2 Microglia Cells From Cytotoxicity Following Oxygen-Glucose Deprivation/Recovery - Zhao, Shen; Xiao, Peng; Cui, Hao; Gong, Ping; Lin, Caijing; Chen, Feng; Tang, Ziren (Frontiers in Molecular Neuroscience, 2020)
ABSTRACT Background: Hypothermia attenuates microglia activation and exerts a potential neuroprotective effect against cerebral ischemic-reperfusion (I/R) injury. However, the underlaying mechanism remains to be elucidated. In this in vitro study, a model of oxygen-glucose deprivation, followed by recovery (OGD/R), was used to investigate whether hypothermia exerts anti-inflammatory and anti-apoptosis properties via enhanced ubiquitination and down-regulation of voltage-dependent anion channel 3 (VDAC3) expression. Methods: BV2 microglia were cultured under OGD for 4 hours following reperfusion with or without hypothermia for 2, 4, or 8 hours. M1 and M2 microglia markers (inducible nitric oxide synthase [iNOS] and arginase [Arg]1) were detected using immunofluorescence. The levels of pro-inflammatory cytokines (tumor necrosis factor [TNF] α, interleukin [IL]-1β) and anti-inflammatory factor (IL-10) were determined using enzyme-linked immunosorbent assay (ELISA). Mitochondrial membrane potential (∆Ψm) was assayed by JC-1 staining using a flow cytometer. Expression of caspase-3, cleaved caspase-3, and VDAC3 were assessed using western blot analysis. The cellular locations and interactions of ubiquitin and VDAC3 were identified using double immunofluorescence staining and immunoprecipitation (IP) assay. In addition, the level of the VDAC3 mRNA was determined using quantitative polymerase chain reaction (qPCR). Results: Hypothermia inhibited the OGD/R–induced microglia activation and differentiation into the M1 type with pro-inflammatory effect, whereas it promoted differentiation to the M2 type with anti-inflammatory effect. Hypothermia attenuated OGD/R-induced loss of ∆Ψm, as well as the expression of apoptosis-associated proteins. Compared to normothermia, hypothermia increased the level of ubiquitinated VDAC3 in the BV2 microglia at both 2 and 8 hours of reperfusion. Furthermore, hypothermia did not attenuate VDAC3 mRNA expression in OGD/R-induced microglia. Conclusions: Hypothermia treatment during reperfusion, attenuated OGD/R-induced inflammation and apoptosis in BV2 microglia. This might be due to the promotion of VDAC3 ubiquitination, identifying VDAC3 as a new target of hypothermia.